Shining a light on the hidden structure of gelatin methacryloyl bioinks using small-angle X-ray scattering (SAXS). (8th October 2021) - Boyd-Moss, Mitchell; Firipis, Kate; O'Connell, Cathal D.; Rifai, Aaqil; Quigley, Anita; Boer, Gareth; Long, Benjamin M.; Nisbet, David R.; Williams, Richard J.
Abstract : Small-angle X-ray scattering is used to unpack the hidden structure of a gelatin methacryloyl (GelMA) biogel. We present insights regarding how the degree of functionalisation, crosslinked polymer conformation, nanoscale mesh size and macroscale mechanical properties are interlinked. Abstract : The challenge with engineering soft materials is to find a chemically functionalized material that can be easily fabricated into complex structures while providing a supportive cellular milieu. The current gold standard is gelatin methacryloyl (GelMA), a semi-synthetic collagen-derived biomaterial that has found widespread utility as a bioink for 3D bioprinting. Although a fundamental understanding of controlling the mechanical properties of GelMA exists, the nano- and cell-scale network topology needs to be investigated to produce controlled structures. Here, for the first time, small-angle X-ray scattering (SAXS) is used to elucidate how structural changes on the network level dictate the final properties within a GelMA hydrogel. Scaffold nanostructure was observed pre- and post-crosslinking, with emphasis on assessing structural changes in response to changes in Degree of Functionalization (DoF) and polymer concentration. Samples were modelled regarding local-polymer conformation (mass fractal dimension), distance between entanglements (correlation length), and mesh size. Importantly, DoF is observed to alter crosslinked polymer conformation and nanoscale mesh size. These results inform future design of GelMA-based bioinks, allowing researchers to further leverage the young and evolving bioprinting technology for broad-spectrum applications such as cell/stem cell printing, organoid-based tissue structure, building cell/organ-on-a-chip, through to the hierarchical engineering of multicellular living systems.